Resilience and the meaning of nurses' work in the COVID-19 pandemic. - Caroccini, Thiago Portela; Neves, Vanessa Ribeiro; Silva, Silmar Maria da; Belasco, Angelica Gonçalves Silva; Baptista, Patricia Campos Pavan; Balsanelli, Alexandre Pazetto (Acta Paulista de Enfermagem, 2024)
Objective: To verify and correlate resilience and meaning of work in hospital nurses during the COVID-19 pandemic. Method: This is a descriptive and correlational study, carried out between June and November 2021, with 164 nurses from two hospitals in São Paulo using the Connor-Davidson Resilience Scale and the Inventário do Significado do Trabalho (Meaning of Work Inventory). The data were analyzed using descriptive and inferential statistics, Pearson's correlation test, Kruskal-Wallis test, Student's t test, Dunn's test, Spearman's correlation test, Univariate Analysis of Variance, Shapiro-Wilk normality test, Levene's test. The statistical significance value adopted was 5% (p ≤ 0.05). Results: Mean age 37.54 years (SD = 8.52), with 81.1% (133) female and mean resilience of 76.98 (SD = 11.32). Significant positive correlations were found between education, age and resilience with the attributes "Source of achievement and economic independence", "Expression of respect and acceptance", "Source of challenge, responsibility and livelihood", "Challenging", "Economic growth", "Feeling pleasure and protection", "Contributing socially and be assisted" and "Being recognized"; Conclusion: There was a correlation between resilience and the meaning of work, helping to face the adversities encountered in the COVID-19 pandemic.